RANCANG BANGUN ALAT PEMARUT DAN PEMERAS SANTAN KELAPA DENGAN MENGGUNAKAN 1 MOTOR PENGGERAK UNTUK MENINGKATKAN EFEKTIFITAS (Infotekmesin, 2018)
There are many of food processing of raw materials are still using a separate tools of coconut grater and squeezer, which causes a long production process. Basically the grater machines on the market only can be used to scrape away the coconut meat. While the tool for extracting the coconut milk is still using coconut sieve and squeezed by hand. The Research initiated with a survey into traditional markets and entrepreneurs of coconut grater services around Semarang. The survey aimed to identify the tools used in the market and the needs of potential users. The survey obtained data of customer’s need that will be used as a reference for developing the concept of making tools. Anthropometric data needed to design the dimensions of the tool, with the purpose of the tool made will be ergonomics and comfortable to be used by the operator. Grater and Squeezer of Coconut Milk Tool which designed has dimensions of 105 cm height and 74 cm width. It has parts: the framework, grater, bleeder screw, motor, gear box, water container, and a pulley / wheel.